Implementasi Matrix Laboratory Dalam Pengolahan Data Mikrotremor Menggunakan Metode Hvsr: Studi Kasus Di Daerah Pesisir Kecamatan Moramo - Sitti Fauziah Faradilla; La Hamimu Hamimu; Laode Ihksan Juarzan (Jurnal Rekayasa Geofisika Indonesia, 2024)
Vibration characteristics in a region of the earth are strongly influenced by unique physical and geological parameters, resulting in diverse responses to natural and anthropogenic disturbances. This research not only contributes to the understanding of geology and vibration response, but also presents a methodology that can be widely applied in passive seismic research. The analysis method in this study uses MATLAB programming language for microtremor signal processing. The algorithm of this research is able to produce a model that reveals the frequency and statistical characteristics of the microtremor signal, the output is quite similar to the open-source software GEOPSY in HVSR processing. There are 15 research data with type .msd as a representation of 15 measurement points scattered in Moramo sub-district. The statistics obtained show that the dominant ground frequency (F0), amplification factor (A0), and seismic susceptibility index (Kg) in the Coastal Land of Moramo Subdistrict range from 0.519792 - 14.692654 Hz, 2.250096 - 6.370357 times amplification, and 0.500194 - 50.516144 s²/cm, respectively. These results are quite similar to previous research by RIVAL (2023) who used GEOPSY software as his analysis tool. The statistical distribution in the form of dominant frequency (F0), amplification (A0) and seismic susceptibility index (Kg) were then interpolated and overlaid with the geodata of the study area using the Mapping Toolbox which is also in the MATLAB environment.